Controlling System for Cloud and Sensor Networks by Authenticated Trust and Reputation Calculation Integration - Vedambika M, Ms.; Rani S, Ms. Soja (IJRDO -Journal of Computer Science Engineering, 2017)
The integration Cloud computing – Wireless sensor network has been attractingthe attention of several researchers both in the academia and the industry as it providesmany opportunities for organizations by offering a range of computing services. So, datagathering capability of wireless sensor networks (WSNs) become easy. For cloudcomputing to become widely adopted by both the enterprises and individuals, several issueshave to be solved. In any case, authentication as well as trust and reputation calculationand management of cloud service providers (CSPs) and sensor network suppliers (SNPs)are two exceptionally critical and barely explored issues for this new paradigm. To fill thegap, our paper proposes a novel authenticated trust and reputation calculation andmanagement (ATRCM) framework for CC-WSN combination or integration. Consideringthe authenticity of CSP and SNP, the attribute necessity of cloud service user (CSU) andCSP, the expense, trust, and reputation of the service of CSP and SNP, the proposedATRCM framework accomplishes the three functions: 1) verifying CSP and SNP to stayaway from malicious impersonation attacks; 2) computing and managing trust andreputation with respect to the service of CSP and SNP; and 3) helping CSU choosedesirable CSP and assisting CSP in selecting suitable SNP. Detailed analysis and design aswell as further functionality evaluation result are presented to exhibit the effectiveness ofATRCM, followed with system security analysis